Implied Volatility and Smile - Rojček, Jakub (2008)
In this work author speaks a little in generic about financial derivatives. Then he derives the famous Black-Scholes formula using less precise mathematical apparatus. Afterwards, he will analyze a few volatility models and their applications for creating volatility surface, which is the main goal of both theoreticians and practitioners. As we will see, the theory is yet very deep but unconsolidated. Nevertheless, praxis has gained some nearly sufficient approaches.